Examining consumer purchase intentions of non-prescription medicines in supermarkets and community pharmacies. (15th November 2018) - Mortimer, Gary; Grimmer, Louise; Fazal-e-Hasan, Syed M
Abstract: Objective: As supermarkets continue to expand their healthcare categories, consumers now have more choice and access to non-prescription medicines. The aim of this current research is to empirically examine the drivers and barriers of consumer purchase intentions, namely trust and perceived risk, of non-prescription medicines in both supermarkets and community pharmacy settings. Method: Data were collected using an in-store intercept survey of 402 supermarket shoppers and 310 community pharmacy shoppers. Confirmatory factor analysis including a measurement and structural model tests were employed using AMOS software package to identify variances in the drivers and barriers of purchase intentions between these retail settings. Key findings: This study found an association between the purchase intention of non-prescription medicines in community pharmacies with their perceived competence, benevolence and provision accurate information . Other than time risk, no other elements of risk were associated with purchase intentions within this setting. In contrast, the perceived risks associated with the purchase of non-prescription medicines within the supermarkets setting – specifically physical and social risk, were present. Results indicate respondents were more likely to intend to purchase medicines from a supermarket if they perceived that the retailer was competent in providing access to safe non-prescription medicines and had the ability to handle transactions. Conclusions: This is the first study to examine the psychological drivers and barriers of purchase intentions of non-prescription medicines in supermarkets and community pharmacies, finding very different results across both retail settings. The study presents a comprehensive model of purchase intentions of non-prescription medicines and recommends directions for pharmacy practitioners and supermarkets.